Perbedaan Kinerja Keuangan Perbankan Pada Bank Pemerintah, Bank Umum Swasta Nasional Devisa, Dan Bank Umum Swasta Nasional Non Devisa Yang Terdapat Di Bursa Efek Indonesia - Linda Rambu Kuba Yowi; Yan Alexander Imanuel Pattisina (Universitas Kristen Wira Wacana Sumba, 2014)
The purpose of this study is to analyze the differences of bank performance in State Bank (Persero), Foreign Exchange National Private Bank, Non-Foreign Exchange National Private Bank in Indonesia Stock Exchange based on a ratio of liquidity, leverage, coverage and profitability. The samples used in this study are 4 state banks, 19 Foreign Exchange National Private Banks and 2 Non-Foreign Exchange National Private Banks. The sampling method is conducted by purposive sampling. Data analysis method used is the One Way Anova test.The results of One Way Anova on liquidity ratio which is represented by the current ratio and a leverage ratio represented by Debt to equity ratio stated that there is no significant difference in the financial performances of the state banks, Foreign Exchange National Private Banks, andNon-Foreign Exchange National Private Banks. While the results of One Way Anova on coverage ratio and profitability ratio represented by ROA shows that there are differences of financial performances in the state banks, Foreign Exchange National Private Banks,and Non-Foreign Exchange National Private BanksKeywords: Financial Performance, Bank